Some conceptual and mythological considerations relating to the construction of an index of social vulnerability with special reference to small island developing states - Briguglio, Pascal Lino (ECLAC Port of SpainTT, 2003)
Discusses the meaning of social vulnerability and reviews the main vulnerability indices. Looks at a number of methodological problems and deals with the strengths and weaknesses associated with indices.